1999
DOI: 10.3758/bf03199432
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from blocking achieved by extinguishing the blocking CS

Abstract: Extinction-induced attenuation of single-phase and two-phase blocking was examined with rats in a conditioned lick-suppression task. In Experiment 1, which compared the effectiveness of single-and two-phase blocking, it was found that single-phase blocking was facilitated by the initiation of training with an A-US trial rather than an AX-UStrial. Single-phase (but not two-phase) blocking was attenuated as a result of 200 extinction trials with the blocking stimulus (Experiment 2). Experiment 3 revealed recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
123
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 30 publications
13
123
1
3
Order By: Relevance
“…The procedure of those experiments was again similar to previous reported studies that have demonstrated a blocking effect (Beckers et al, 2006;Blaisdell et al, 1999;Wheeler et al, 2008) (see Table A3 in Appendix A for a comparison with those previous studies and Table B1 and C1 in Appendix B and C, respectively, for an overview of the stimuli and procedure used in this series).…”
Section: General Overviewmentioning
confidence: 72%
See 2 more Smart Citations
“…The procedure of those experiments was again similar to previous reported studies that have demonstrated a blocking effect (Beckers et al, 2006;Blaisdell et al, 1999;Wheeler et al, 2008) (see Table A3 in Appendix A for a comparison with those previous studies and Table B1 and C1 in Appendix B and C, respectively, for an overview of the stimuli and procedure used in this series).…”
Section: General Overviewmentioning
confidence: 72%
“…Effect size Blaisdell et al, 1999. Cohen's d = 1.79, based on estimations of means and standard deviations for the two-phase blocking and control group.…”
Section: Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In phase 3 of training, A is presented alone. Recovery from blocking is observed when, following all three phases of training, B behaves as a conditioned exciter of X (e.g., Blaisdell, Gunther, & Miller, 1999). The result is surprising inasmuch as learning of the B ➔ X relationship is blocked following phase 2 of training but is later expressed following extinction of the unblocked cue.…”
Section: Section 5: Retrospective Revaluationmentioning
confidence: 88%
“…Minerva-AL has trouble with peak shift (see McLaren, Bennett, Guttman-Nahir, Kim, & Mackintosh, 1995). Minerva-AL predicts that some examples of retrospective revaluation (e.g., backward blocking) ought to be strong and reliable when, in fact, retrospective revaluation is experimentally elusive (see Blaisdell et al, 1999;Dopson, Pearce, & Haselgrove, 2009;Holland, 1999). Minerva-AL fails to acknowledge mediated conditioning due to its explanation for retrospective revaluation-a confusion recognized elsewhere (see Dwyer, 1999;Graham, Jie, Chan, McLaren, & Wills, 2011).…”
Section: Discussionmentioning
confidence: 99%